Estudos das interações de quitosana/CTAB/C12E8 - Santos, Zilvam Melo dos (2013)
Surfactant-polymer interactions are widely used when required rheological properties for specific applications, such as the production of fluids for oil exploration. Studies of the interactions of chitosan with cationic surfactants has attracted attention by being able to cause changes in rheological parameters of the systems making room for new applications. The commercial chitosan represents an interesting alternative to these systems, since it is obtained from partial deacetylation of chitin: the residues sites acetylated can then be used for the polymer-surfactant interactions. Alkyl ethoxylated surfactants can be used in this system, since these non-ionic surfactants can interact with hydrophobic sites of chitosan, modifying the rheology of solutions or emulsions resultants, which depends on the relaxation phenomenon occurring in these systems. In this work, first, inverse emulsions were prepared from chitosan solution as the dispersed phase and cyclohexane as the continuous phase were, using CTAB as a surfactant. The rheological analysis of these emulsions showed pronounced pseudoplastic behavior. This behavior was attributed to interaction of "loops" of chitosan chains. Creep tests were also performed and gave further support to these discussions. Subsequently, in order to obtain more information about the interaction of chitosan with non-ionic surfactants, solutions of chitosan were mixed with C12E8 and and carried out rheological analysis and dynamic light scattering. The systems showed marked pseudoplastic behavior, which became less evident when the concentration of surfactant was increased. Arrhenius and KWW equations were used to obtain parameters of the apparent activation energy and relaxation rate distribution, respectively, to which were connected to the content of surfactant and temperature used in this work